Analisis Fenomena Hedonisme di Kalangan Mahasiswa Penerima Beasiswa KIP Kuliah: Perspektif Sosio-Ekonomi Baru - Ciek Julyati Hisyam; Husnul Khotimah; Kartika Dewi; Santika Virdi (Populer: Jurnal Penelitian Mahasiswa, 2024)
This research aims to explore the phenomenon of hedonism among recipients of the Kartu Indonesia Pintar Kuliah (KIPK) scholarship from a new socio-economic perspective. Using a qualitative approach with in-depth interview methods, this study was conducted at Universitas Negeri Jakarta in May 2024. A total of 8 students, both KIPK recipients and non-recipients, were purposively selected as informants. Data collection techniques were carried out through face-to-face interviews or communication media using structured interview guidelines. The data obtained were then thematically analyzed to identify patterns, differences, and key factors influencing the hedonism phenomenon among KIPK recipients. The research results reveal that social pressure, campus environment, social media, ineffective financial management, and lack of financial education are the main driving factors of consumptive behavior among KIPK scholarship recipients. The findings also identify negative impacts such as misuse of funds, social jealousy, and misalignment in the implementation of the scholarship program. This research provides important insights to enhance the effectiveness of financial aid programs through a more holistic and sustainable approach.